Effects of different carbohydrate sources on activity of rumen microbial enzymes and nitrogen retention in sheep fed diet containing recycled poultry bedding. Issue 1 (1st January 2018) - Azizi-Shotorkhoft, Ayoub; Sharifi, Afrooz; Azarfar, Arash; Kiani, Ali
ABSTRACT: In a completely randomized design, 15 male Moghani sheep were fed to determine the influence of supplementing recycled poultry bedding (RPB) with different carbohydrate sources on the activities of rumen hydrolytic enzymes and nitrogen retention. In the first diet, corn and barley were used as the carbohydrate sources (M0). In the second and third diets, corn and barley were replaced by 50 (M50 diet) and 100 (M100 diet) g/kg of sugar beet molasses, respectively. The extracellular activity of carboxymethyl-cellulase (CMCase) was increased linearly by dietary inclusion of molasses [linear (L), P  < .05]. The extracellular and total activity of microcrystalline-cellulase in ruminal content was increased linearly (L, P  < .05), while its cellular activity remained unaffected ( P  > .05) by dietary inclusion of molasses. Dietary inclusion of molasses in RPB-containing diets linearly increased filter paper degrading (FPD) activity in all fractions of ruminal content (L, P  < .05). Addition of molasses to the diets linearly decreased (L, P  = .04) total activity of α-amylase, and cellular and total activity of proteases. Increasing dietary levels of molasses linearly increased retained N (L, P  < .05). In conclusion, dietary supplementation of RPB-containing diet with molasses improved activities of fibrolytic enzymes and nitrogen retention in sheep.